BLUEBERRY JUICE ENCAPSULATED ON MALTODEXTRIN: THE IMPACT ON THE PROPERTIES OF WHITE CHOCOLATE - Lončarević, Ivana; Stožinić, Milica; Pajin, Biljana; Nikolić, Ivana; Petrović, Jovana; Šojić, Branislav; Zarić, Danica (Food and Feed Research, 2023)
The lower content of phenolic compounds in white chocolate makes this confectionery product unhealthier and, thus, adequate for enrichment compared to other types of chocolates like dark or milk. Less phenolics in white chocolate is due to absence of dark cocoa solids, abundant in these compounds. This study aimed to develop a new product with a higher nutritional value than regular white chocolate by enriching white chocolate with blueberry juice as a natural source of polyphenols. Since phenolic compounds are highly sensitive to heat, light, oxygen, and pH, encapsulated form of blueberry juice was used to increase their stability in the product. Blueberry juice was encapsulated on maltodextrin (B/M) and added to white chocolate at 80 g/kg and 100 g/kg concentrations. Enrichment significantly (p